Transient Offset in 14C After the Carrington Event Recorded by Polar Tree Rings - Uusitalo, Joonas; Golubenko, Kseniia; Arppe, Laura; Brehm, Nicolas; Hackman, Thomas; Hayakawa, Hisashi; Helama, Samuli; Mizohata, Kenichiro; Miyake, Fusa; Mäkinen, Harri; Nöjd, Pekka; Tanskanen, Eija; et al. (John Wiley & Sons, 2024)
The Carrington event of 1859 has been the strongest solar flare in the observational history. It plays a crucial role in shedding light on the frequency and impacts of the past and future Solar Energetic Particle (SEP) events on human societies. We address the impact of the Carrington event by measuring tree-ring 14C with multiple replications from high-latitude locations around the event and by comparing them with mid-latitude measurements. A transient offset in 14C following the event is observed with high statistical significance. Our state-of-the-art 14C production and transport model does not reproduce the observational finding, suggesting features beyond present understanding. Particularly, our observation would require partially fast transport of 14C between the stratosphere and troposphere at high latitudes. The observation is consistent with the previous findings with the SEP events of 774 and 993 CE for which faster integration of 14C into tree rings is observed at high latitudes.
Keywords: solar flares; dendrochronology; subarctic zone; stratosphere; troposphere